2004
DOI: 10.1002/hipo.10183
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal function in posttraumatic stress disorder

Abstract: Recent studies have reported memory deficits and reduced hippocampal volumes in posttraumatic stress disorder (PTSD). The goal of the current research was to use functional neuroimaging and a validated explicit memory paradigm to examine hippocampal function in PTSD. We used positron emission tomography (PET) and a word-stem completion task to study regional cerebral blood flow (rCBF) in the hippocampus in 16 firefighters: 8 with PTSD (PTSD group) and 8 without PTSD (Control group). During PET scanning, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(157 citation statements)
references
References 87 publications
10
135
3
7
Order By: Relevance
“…Functional neuroimaging findings using positron emission topography (PET) and functional magnetic resonance imaging (fMRI) suggest that individuals with PTSD exhibit hyperresponsive amygdala activity to trauma or fear-related stimuli (for review, see Shin and Liberzon, 2010), during emotionally neutral tasks (Bryant et al, 2005;Shin et al, 2004b), and even at rest (Chung et al, 2006;Semple et al, 2000). A hyperresponsive amygdala contributes to the exaggerated fear response characteristic of PTSD (Anderson et al, 2003).…”
Section: Clinicalmentioning
confidence: 99%
“…Functional neuroimaging findings using positron emission topography (PET) and functional magnetic resonance imaging (fMRI) suggest that individuals with PTSD exhibit hyperresponsive amygdala activity to trauma or fear-related stimuli (for review, see Shin and Liberzon, 2010), during emotionally neutral tasks (Bryant et al, 2005;Shin et al, 2004b), and even at rest (Chung et al, 2006;Semple et al, 2000). A hyperresponsive amygdala contributes to the exaggerated fear response characteristic of PTSD (Anderson et al, 2003).…”
Section: Clinicalmentioning
confidence: 99%
“…Among those 26 studies, 16 reported a smaller hippocampus in PTSD in at least one hemisphere. Of those 16, 10 tested memory, but in one case, this was a test of implicit memory (Shin et al, 2004 ). Of the 9 studies testing declarative memory, 2 did not report whether group differences were found, and only 4 reported signifi cantly worse memory in PTSD.…”
Section: Symposiummentioning
confidence: 99%
“…Impairment of hippocampal function is also suggested from functional magnetic resonance imaging (fMRI) studies, in which the activity of brain regions is extrapolated from blood flow changes over time. For example, when engaged in verbal learning tasks PTSD patients demonstrate lower levels of hippocampal activation than matched non-PTSD control subjects Shin et al, 2004). Sustained treatment of PTSD for several months with the antidepressant paroxetine produced increases in hippocampal volume and cognitive function .…”
Section: Hippocampusmentioning
confidence: 97%